An Exploration of the Relationship between High Performance Work Systems and Job Satisfaction - Afcha, Sergio (2015)
This paper contains an exploration of the relationship between high performance work systems (HPWSs) and employee wellbeing for workers from European countries. Specifically, the focus is on an examination of the level of involvement from firms using HPWSs in the different aspects of work organization. The results provided empirical evidence about the influence of factors like autonomy, flexibility, teamwork and skills, and workers’ on-the-job satisfaction. The results indicated that higher levels of involvement in some HPWS practices increased the level of job satisfaction. In addition, estimates by age reveal interesting differences in the self-perception of job satisfaction.